2019
DOI: 10.1002/pds.4847
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risks associated with dipeptidyl peptidase‐4 inhibitors monotherapy compared with other antidiabetes drugs in the Japanese population: A nationwide cohort study

Abstract: Purpose We evaluated the cardiovascular risk associated with dipeptidyl peptidase‐4 inhibitors (DPP‐4Is) as monotherapy compared with other antidiabetic drugs in Japan. Methods We conducted a nationwide cohort study involving 2 716 000 diabetes patients in Japan. New users of any antidiabetic drug as monotherapy between 1 April 2010 and 31 October 2014 were identified. Occurrences of myocardial infarction (MI), heart failure (HF), and stroke requiring hospitalization associated with DPP‐4Is were compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 29 publications
1
10
1
Order By: Relevance
“…Our results on the risk of cardiovascular events are consistent with those of previous Japanese studies that also used claims databases,13 14 where the effect on reduction in the event tended to be lower with biguanide than with DPP-4i as the first-line therapy. However, there are some differences in the study methods.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our results on the risk of cardiovascular events are consistent with those of previous Japanese studies that also used claims databases,13 14 where the effect on reduction in the event tended to be lower with biguanide than with DPP-4i as the first-line therapy. However, there are some differences in the study methods.…”
Section: Discussionsupporting
confidence: 91%
“…However, there are some differences in the study methods. In a 2019 study, a significant difference was observed in the reduction in the incidence of MI and HF with metformin as the first-line monotherapy 14 ; however, in the current study, a significant difference was not observed in the MDV database, and a significant difference was observed only for MI in the JMDC database during the entire study period. For the period of monotherapy, which is the same as that of the previous study, no significant difference was observed in both databases.…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…The NDB is a nationwide database in Japan operated by the MHLW, and contains the electronic claims data covering almost all Japanese individuals (−120 million) and special health check-up data since April 2009. 21 MID-NET® is a new medical information database network that is known to be a reliable and valuable database in Japan and stores EMRs, administrative claim data, and DPC data of over 5.3 million patients (as of December 2020) in cooperation with 10 healthcare organizations, including 23 university hospitals or core regional hospitals. 22 The purpose of these studies was to investigate the actual drug use or safety risks associated with a drug in clinical practice.…”
Section: Cases At Postapproval Stagementioning
confidence: 99%